Synthesis and Antimicrobial Activity of 4H, 4-Thio-2-hepta-O-benzoyl-b-D-lactosylimino- 3-phenyl-2,3-dihydro-(1,3,5)-triazino-(2,1b) 6, 7 or 8-Aryl benzothiozoles (hydrochlorides) - Heda, K.M.; Deshmukh, S.P. (Asian Journal of Chemistry, 2013)
A series of novel 4H, 4-thio-2-hepta-O-benzoyl-b-D-lactosylimino-3-phenyl-2,3-dihydro-(1,3,5)-triazino-(2,1b) 6,7 or 8 aryl benzothiozoles (hydrochlorides) have been synthesized by the interaction of several 1-hepta-O-benzoyl-b-D-lactosyl-3-aryl benzothiozolyl thiocarbamides with N-phenyl isocyanodichloride. These compounds were screened for their antibacterial and antifungal activities against-Escherichia coli, Proteus vulgaris, Staphylococcus aureus, Salmonella typhimurium, Klebsiella pneumonie, Psudomonas aeruginosa, Aspergillus niger and Candida albicance. The newly synthesized compounds have been characterized by analytical and IR, 1H NMR and mass spectral studies.